Perhitungan Neraca Air Meteorologi Waduk Jatiluhur Berdasarkan Data Curah Hujan Dan Penguapan - Muhammad Asnawi; Rheinhart Christian Hamonangan Hutauruk (Buletin GAW Bariri, 2022)
One of the causes of water reduction in reservoirs is the large evaporation caused by rainfall. Measurements of the amount of evaporation in the reservoir still need to be tested and adjusted to local conditions of the region. Hence the calculation of Jatiluhur reservoir water balance is based on precipitation data and evaporation with the aim to obtain potential evaporation formula and to know the surplus and water deficit in Jatiluhur reservoir due to climatology factor. The data used is daily rainfall data and daily evaporation data from 2003 to 2018. The research begins with grouping rainy days, no rainy days and evaporation every month. Furthermore the data is divided into several classes for the later specified frequency and maximum and minimum value of evaporation data. Then the calculation is calculated evaporation and potential lost with empirical formula based on maximum, minimum, and predefined values. The result is a large potential evaporation when the rainy day and the rainy day from January to December in Jatiluhur Reservoir is generally in the range of 3.8 to 11 mm/day, except in August and September are experiencing a significant increase. Next, the potential loss of Jatiluhur reservoirs in each month can be sought using empirical formulas with variable rainfall, evaporation when rainy day and day without rain.